KECEKAPAN PENGURUSAN KEWANGAN DAN AGIHAN ZAKAT: KAJIAN DI MAJLIS UGAMA ISLAM SABAH (MUIS): Efficiency of Financial and ZakÄh Distribution Management: A Study at Sabah Islamic Religious Council (MUIS) - Ag Omar, Pg Mohd Faezul Fikri; Wahid, Hairunnizam; Mohd Nor, Mohd Ali (Jurnal Syariah, 2017)
A strong financial performance for Majlis Agama Islam Negeri is crucial for determining the efficacy of the institution’s operations, particularly in zakāh collection and distribution. An efficient financial management over zakāh distribution is important for eradicating poverty and ensuring future development of a society. On the other hand, the inefficiency of zakāh distribution by the zakāh institutions in Malaysia could negatively affect Muslims towards paying zakāh subsequently the performance of said institutions. As reported in previous research, it has been observed that an excess of zakāh funds remain undistributed every year to eight categories of asnaf. As such, this study examines the efficacy of MUIS financial management as well as of zakāh distribution by Pusat Zakat Sabah (PZS-MUIS); using the secondary data collected from MUIS financial report from 2000 to 2013. Several cash flow ratios were used as a proxy for financial performance, as well as the data for zakāh distribution. The results of ratio analyses indicate that there have been significant enhancements in financial and zakāh distribution during by both MUIS and PZS-MUIS during the period of this study, even though the efficiency scores obtained are inconsistent. This study suggests that both MUIS and PZS-MUIS have to maintain and enhance their performance for the future. This study shows that both financial and zakāh distribution management performance need to be achieved simultaneously for optimal zakāh distribution and offers several recommendations.